SYNTHESIS OF BIOMATERIAL-GRADE WHITLOCKITE FROM CRAB SHELL WASTE: AN ECO-FRIENDLY APPROACH - Khumaera, Rahmatia; Sirait, Maria Diva Yuniar; Rahim, Muhammad; Putri, Rezky Meyvia; Sumual, Theofilus Ariel; Musyarofah, Musyarofah (Universitas Mataram, 2025)
Crab shells, rich in calcium carbonate (CaCO3), provide a sustainable source of calcium oxide (CaO) for synthesizing Whitlockite (WH, Ca9(MgFe)(PO4)6PO3H), a potential biomaterial for bone replacement. This study addresses prior research gaps by exploring synthesis temperature variations from 700℃ to 1000℃ and employing acid precipitation to yield high-purity WH. Characterization was performed using Fourier Transform Infrared (FT-IR), X-ray Diffraction (XRD), X-ray fluorescence (XRF), Scanning Electron Microscopy (SEM), and Brunauer Emmet-Teller (BET) analysis. Results indicate that the crab shell powder contains 99.0944%wt. The XRD results show that optimal crystallinity and purity of WH were achieved at a calcination temperature of 900℃. The FTIR test results show that the functional groups of WH at calcination temperatures of 700℃, 800℃, 900℃, and 1000℃ for 5 hours are detected in specific wave ranges, namely PO₄³- (673-671 cm-¹), and OH- (3340-3198 cm-¹), which contribute to the bone formation process. SEM tests revealed that changes in calcination temperature affected the morphology of WH, with the optimal temperature producing a smaller size, minimal agglomeration, and a more uniform size distribution. BET analysis showed that 900℃ gave the highest adsorption capacity and good stability, indicating a more significant potential for interaction with body cells. These findings confirm the ability of WH to be a promising biomaterial for bone replacement applications.